PROTEIN DIGESTION IN PERANAKAN ETAWA GOAT DUE TO DIFFERENT LEVELS OF DIETARY PROTEIN - Yusuf, Roosena (BIOMA, 2014)
The effort to increases milk production especially milk goat production can do with increasing quality of dietary and maintenance of goats, one of them was increasing level of dietary protein to increase protein metabolism in goats. The research purpose was to find out the acurate of dietary protein level to maximalize protein digestion in Peranakan Etawa goat. The materials used in the research were 12 Peranakan Etawa goats at fourth month pregnancy and range of body weight 35,20 ± 1,21 kg (cv = 3,44%) with ± 13 month ages. The research design that used is completely randomized design one factor with three treatment and four restating. Parameter that evaluated include dry matter intake, consumption of crude protein, protein digestion. Result of the research shown that the average of dry matter intake to T1, T2 and T3 were 958,99; 981,51 and 1242,73 g/goat/day (P<0,05). The average of consumption of crude protein to T1, T2 and T3 were 114,69; 144,44 and 233,11 g/goat/day(P<0,05). The average of protein digestion to T1, T2 and T3 were 64,22 (55,18%); 92,83 (64,21%) and 156,21 (66,97%) g/goat/day (P<0,05). The conclution of the research was levels of dietary protein as 18,43% may increase the optimal protein digestion in Peranakan Etawa goat.Keywords : protein, Peranakan Etawa goat